Race, rhetoric, and technology : searching for higher ground - Banks, Adam J. (NCTE-LEA research series in literacy and composition, 2006)
"In this book Adam Banks uses the concept of the Digital Divide as a metonym for America's larger racial divide, in an attempt to figure out what meaningful access for African Americans to technologies and the larger American society can or should mean. He argues that African American rhetorical traditions - the traditions of struggle for justice and equitable participation in American society - exhibit complex and nuanced ways of understanding the difficulties inherent in the attempt to navigate through the seemingly impossible contradictions of gaining meaningful access to technological systems with the good they seem to make possible and at the same time resisting the exploitative impulses that such systems always seem to present."--BOOK JACKET.